ANALYSIS OF STANDARD OPERATING PROCEDURES (SOPS) ON CUPPING THERAPY IN DKI HEALTH SERVICES, JAKARTA - Tri Wahyuni Lestari; Annisa Rizky Afrilia; Nita Prihartini (International Islamic Medicine Forum, 2020)
Traditional cupping therapy is an alternative therapy that is invasive in society. The Indonesian Cupping Association (PBI) has established a Standard Operating Procedure (SPO) as a guide for its practitioners in service. In this study, an analysis of the SPO items was evaluated on 30 cupping practitioners in the DKI Jakarta area. This study aims to obtain an overview of the SPO with easy, medium, and difficult categories that can be fulfilled by cupping practitioners and are expected to provide input to the Standard Cupping Operational Procedure module. Methods: This study was a cross-sectional study , conducted on 30 cupping practitioners in DKI Jakarta who met the inclusion and exclusion criteria. The data collection method was done by observing cupping practitioners three times each to avoid bias in their behavior. In addition, interviews were also conducted with 30 clients who use cupping services to assess SPO's impression. Data analysis explained descriptively. Results show that there were SPO activities in the Standard Cupping Operational Procedure module with an easy category of 64.5%, a moderate category of 14.5%, and a difficult category of 21%. There are easy categories that mean infrastructure, namely 72.7%, 13.6% moderate category, and difficult category of 13.6%. The conclusion contained in the SPO are included in the easy category. However, SPO items still need attention and supervision, especially SPO items with medium and difficult categories.